Pencarian Terjemahan Hadits Shahih Muslim menggunakan Metode BM-25 - Bagus Abdan Aziz Fahriansyah; Indriati Indriati; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Hadits is second reference to moslem people. Furthermore function of hadits is explanation from alquran . but many common people difficult to find some topic of hadits because its amount very much and not everyone can memorize it. Actually paper book or electronic book can't give feedback which relevant first. In computer science there's subject that study about extracting words become a new information that we need or to know similarity a phrase with certain document namely text mining. writer wants implement one of text mining technique namely BM-25 in searching of hadits shahih moeslem . and writer wants to know how effective BM-25 algorithm for handle problem that writer give. From research that using hadits shahih moeslem as its data. Writer wants testing with five different queries and made variate of value of k and b variable that can optimize the result of query dan k variable optimum at q1=0.75 ; q2=0.5 ; q3=0.75 ; q4=0.75 ; q5=0.5 and b variable optimum at q1=0.1.2 ; q2=1.2 ; q3=1.2; q4=1.2; q5=1.2 and precision @ k that gets average precision value p@10=70%,p@20=54%,p@30=42%.